Pretreatment of extruded Napier grass by hydrothermal process with dilute sulfuric acid and fermentation using a cellulose-hydrolyzing and xylose-assimilating yeast for ethanol production. (January 2022) - Ismail, Ku Syahidah Ku; Matano, Yuki; Sakihama, Yuri; Inokuma, Kentaro; Nambu, Yumiko; Hasunuma, Tomohisa; Kondo, Akihiko
Graphical abstract: Highlights: Extrusion of Napier grass alone resulted in 30.2% lignin removal. The best pretreatment condition was at 190 °C, 3% sulfuric acid, for 30-min. Ethanol yield of 0.26 g-ethanol/g-biomass was achieved using cell-surface displaying S. cerevisiae. The amount of commercial enzyme used was successfully reduced. Abstract: One of the potential bioresources for bioethanol production is Napier grass, considering its high cellulose and hemicellulose content. However, the cost of pretreatment hinders the bioethanol produced from being economical. This study examines the effect of hydrothermal process with dilute acid on extruded Napier grass, followed by enzymatic saccharification prior to simultaneous saccharification and co-fermentation (SScF). Extrusion facilitated lignin removal by 30.2 % prior to dilute acid steam explosion. Optimum pretreatment condition was obtained by using 3% sulfuric acid, and 30-min retention time of steam explosion at 190 °C. Ethanol yield of 0.26 g ethanol/g biomass (60.5% fermentation efficiency) was attained by short-term liquefaction and fermentation using a cellulose-hydrolyzing and xylose-assimilating Saccharomyces cerevisiae NBRC1440/B-EC3-X ΔPHO13, despite the presence of inhibitors. This proposed method not only reduced over-degradation of cellulose and hemicellulose, but also eliminated detoxification process and reduced cellulase loading.